If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy(5xy) + 3xy(1) = 0 Remove parenthesis around (5xy) 3xy * 5xy + 3xy(1) = 0 Reorder the terms for easier multiplication: 3 * 5xy * xy + 3xy(1) = 0 Multiply 3 * 5 15xy * xy + 3xy(1) = 0 Multiply xy * xy 15x2y2 + 3xy(1) = 0 Reorder the terms for easier multiplication: 15x2y2 + 3 * 1xy = 0 Multiply 3 * 1 15x2y2 + 3xy = 0 Reorder the terms: 3xy + 15x2y2 = 0 Solving 3xy + 15x2y2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3xy'. 3xy(1 + 5xy) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'xy' equal to zero and attempt to solve: Simplifying xy = 0 Solving xy = 0 Move all terms containing x to the left, all other terms to the right. Simplifying xy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(1 + 5xy)' equal to zero and attempt to solve: Simplifying 1 + 5xy = 0 Solving 1 + 5xy = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5xy = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5xy = 0 + -1 5xy = 0 + -1 Combine like terms: 0 + -1 = -1 5xy = -1 Divide each side by '5y'. x = -0.2y-1 Simplifying x = -0.2y-1Solution
x = {-0.2y-1}
| 16t^2+150t+20=0 | | 5x+2=36 | | .5x-.625=.75x+.375 | | 2x(x-4)+x(3-2x)= | | 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 |